Persistent Gaps, Volatility Types, and Default Traps - Fostel, Ana (IMF Working Papers; Working Paper ;, 2007)
We show that cross-country differences in the underlying volatility and persistence of macroeconomic shocks help explain two historical regularities in sovereign borrowing: the existence of "vicious" circles of borrowing-and-default ("default traps"), as well as the fact that recalcitrant sovereigns typically face higher interest spreads on future loans rather than outright market exclusion. We do so in a simple model where output persistence is coupled with asymmetric information between borrowers and lenders about the borrower's output process, implying that a decision to default reveals valuable information to lenders about the borrower's future output path. Using a broad cross-country database spanning over a century, we provide econometric evidence corroborating the model's main predictions-namely, that countries with higher output persistence and conditional volatility of transient shocks face higher spreads and thus fall into default traps more easily, whereas higher volatility of permanent output tends to dampen these effects.